2020
DOI: 10.1111/aor.13877
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo assessment of erythrocyte tolerance to the HeartWare ventricular assist device operated in three discrete configurations

Abstract: Despite technological advances in ventricular assist devices (VADs) to treat end‐stage heart failure, hemocompatibility remains a constant concern, with supraphysiological shear stresses an unavoidable reality with clinical use. Given that impeller rotational speed is related to the instantaneous shear within the pump housing, it is plausible that the modulation of pump speed may regulate peak mechanical shear stresses and thus ameliorate blood damage. The present study investigated the hemocompatibility of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
4
1
Order By: Relevance
“…Thus, in a chronological sense, our results are in agreement with those of Woelke et al ., 6,7 although our data extend these observations; our congruence of results from the three loops were achieved despite differences in the two most extreme conditions varying by 240 ml and 192 minutes (Figure 2B). The mean NIH observed in the present study ranged 4.2–4.9 mg·100 L c1 , which is mildly lower than prior reports of 5.3, 10 6.8, 11 and 7 12 mg·100 L −1 ; our hypothesis is that our venesection technique, and rapid use of blood following collection may explain, at least in part, this observation. Nevertheless, it is encouraging that the tight range of NIH values in the present study, despite the substantially different loop volumes, provides confidence in further evaluation of smaller blood test loops for accelerated hemolysis assessment.…”
Section: Discussioncontrasting
confidence: 81%
“…Thus, in a chronological sense, our results are in agreement with those of Woelke et al ., 6,7 although our data extend these observations; our congruence of results from the three loops were achieved despite differences in the two most extreme conditions varying by 240 ml and 192 minutes (Figure 2B). The mean NIH observed in the present study ranged 4.2–4.9 mg·100 L c1 , which is mildly lower than prior reports of 5.3, 10 6.8, 11 and 7 12 mg·100 L −1 ; our hypothesis is that our venesection technique, and rapid use of blood following collection may explain, at least in part, this observation. Nevertheless, it is encouraging that the tight range of NIH values in the present study, despite the substantially different loop volumes, provides confidence in further evaluation of smaller blood test loops for accelerated hemolysis assessment.…”
Section: Discussioncontrasting
confidence: 81%
“…Of these publications, only primary sources of experimental hemolysis were included (n = 9). 6,[27][28][29][30][31][32][33][34] As a common comparative measure for reproducibility, the absolute coefficient of variation (CV) was calculated, which is the ratio of the standard deviation to the mean value of a series of measurements. The CV was calculated separately for all reported test conditions, totaling 31 collected measurement series with an average of 51 ± 30%.…”
Section: The Reproducibility Challengementioning
confidence: 99%
“…The pivotal MOMENTUM 3 study reported a significantly improved net hemocompatibility score for HM3 as compared to HM2, with such improvement linked to the absence of observed hemolysis 48 . The HVAD system, which was reported to induce hemolysis compared to static sample 49 , also showed less induced hemolysis when compared to HM2 50 . Other work, however, reported elevated shear stress and shear rate in the aortic arch with the HVAD when compared to both HMII and HM3 51 .…”
Section: Discussionmentioning
confidence: 88%